2014
DOI: 10.1186/s12968-014-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of myocardial T2 and T1 against iron concentration

Abstract: BackgroundThe assessment of myocardial iron using T2* cardiovascular magnetic resonance (CMR) has been validated and calibrated, and is in clinical use. However, there is very limited data assessing the relaxation parameters T1 and T2 for measurement of human myocardial iron.MethodsTwelve hearts were examined from transfusion-dependent patients: 11 with end-stage heart failure, either following death (n = 7) or cardiac transplantation (n = 4), and 1 heart from a patient who died from a stroke with no cardiac i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…Recently, it has been shown that myocardial T2 correlates well with myocardial iron concentration. This raises the possibility that T2 may provide additive information to T2* for patients with myocardial siderosis in the future …”
Section: Cardiac Siderosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that myocardial T2 correlates well with myocardial iron concentration. This raises the possibility that T2 may provide additive information to T2* for patients with myocardial siderosis in the future …”
Section: Cardiac Siderosismentioning
confidence: 99%
“…This raises the possibility that T2 may provide additive information to T2* for patients with myocardial siderosis in the future. 94…”
Section: Cardiac Siderosismentioning
confidence: 99%
“…It mainly alters T2 relaxation, an inherent tissue characteristic, by creating focal magnetic field inhomogeneities that cause fast proton dephasing and signal decay. Myocardial T2 can be directly measured by CMR and reflects iron concentration . Preliminary experience with myocardial T2 measurements in humans with iron overload was not satisfactory, as the spin echo sequence used was very susceptible to cardiac and respiratory motion .…”
Section: Assessing the Heart In β‐Thalassemia Major: The Role Of Cmrmentioning
confidence: 99%
“…Linking cardiac siderosis measured by T2* to therapy improves outcome in Thalassemia Major. Aim of our study is to compare T1 mapping (Modified Lock Locker Inversion recovery, MOLLI) to dark (DB) and bright (BB) blood T2* [3][4] in cardiac iron overload and to support the hypothesis that T1 mapping has higher sensibility to T2* for small amount of iron, which would make it a complementary tool to T2* in borderline iron overload patients. [5][6] Methods In a prospectively large single centre study of 138 Thalassemia Major patients and 32 healthy controls, we compared MOLLI to DB and BB T2* acquired on an Avanto 1.5T scanner (Siemens Healthcare, Erlangen, Germany).…”
mentioning
confidence: 99%